Lock‐in thermography as a tool for quality control of photovoltaic modules. Issue 1 (2nd April 2013) - Vetter, Andreas; Fecher, Frank; Adams, Jens; Schaeffler, Raymund; Theisen, Jean‐Patrick; Brabec, Christoph J.; Buerhop, Claudia
Abstract In this short communication, we present a method which utilizes contactless ILIT (illuminated lock‐in thermography) measurement of a photovoltaic (PV) module and image postprocessing in order to calculate the peak power Pmpp of the module and to study the influence of local defects on the module performance. In total, 103 Copper‐Indium‐Gallium‐Diselenide (CIGS) modules were investigated and the results showed a good correlation (mean error less than 6%) between the calculated IR‐signal and the measured Pmpp. We performed our study on CIGS modules but the presented approach is not restricted to CIGS modules. The method provides a valuable tool for PV quality control.